The Influence of Perceived Value, Trust, Hedonic Motivation, and Consumer Attitudes on Purchasing Intentions of Korean Skincare Products in Surabaya - Putri, Prisca Serenata; Suryani, Tatik (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2025)
This research analyzed and influenced perceived value, trust, hedonic motivation, and consumer attitudes on purchasing intentions for Korean skincare products in Surabaya. This research was conducted on consumers interested in buying Korean skincare products with a total population of 188 respondents. The sample used was 150 respondents because some samples did not match the criteria. The data collection technique used was a questionnaire via Google Forms. The variable measurement uses a Likert scale with analysis techniques using SEM-PLS with the Smart-PLS application ver 3.0. The results of the research show that: Perceived value has a significant effect on consumer attitudes. Consumer attitudes have a significant effect on purchase intentions. Perceived value has a significant effect on purchase intentions. Consumer attitudes have a significant mediating effect on the perceived value of purchase intentions. Hedonic motivation has a significant effect on consumer attitudes. Hedonic motivation has a significant effect on purchase intention, Consumer attitude has no significant effect mediating hedonic motivation on purchase intention, Trust has a significant effect on consumer attitude, Trust has no significant effect on purchase intention, and Consumer attitude mediates the effect of trust on purchase intention.